1999
DOI: 10.1002/(sici)1097-4652(199906)179:3<297::aid-jcp7>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, a natural product derived from grape, exhibits antiestrogenic activity and inhibits the growth of human breast cancer cells

Abstract: Resveratrol is a natural phytoalexin compound found in grapes and other food products. In this study, the effect of resveratrol on the growth of human breast cancer cells was examined. Results show that resveratrol inhibits the growth of estrogen receptor(ER)-positive MCF-7 cells in a dose-dependent fashion. Detailed studies with MCF-7 cells demonstrate that resveratrol antagonized the growth-promoting effect of 17-beta-estradiol (E2) in a dose-dependent fashion at both the cellular (cell growth) and the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
166
4
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(188 citation statements)
references
References 45 publications
17
166
4
1
Order By: Relevance
“…MCF-7 cells were cultured in a 1:1 mixture of DMEM and Ham's F-12 medium supplemented with 5% (vol͞vol) FBS. One day before the start of the experiment, the medium was changed to E 2 -depleted PFMEM (phenol red-free ␣-MEM) supplemented with 5% charcoal-extracted FBS as described (15). Twenty-four hours later, the medium was replaced with PFMEM.…”
supporting
confidence: 59%
“…MCF-7 cells were cultured in a 1:1 mixture of DMEM and Ham's F-12 medium supplemented with 5% (vol͞vol) FBS. One day before the start of the experiment, the medium was changed to E 2 -depleted PFMEM (phenol red-free ␣-MEM) supplemented with 5% charcoal-extracted FBS as described (15). Twenty-four hours later, the medium was replaced with PFMEM.…”
supporting
confidence: 59%
“…In relation to this, others have also shown that resveratrol exhibits various degrees of estrogenic effects (Gehm et al 1997). However, there are other more recent investigations that question whether resveratrol has any significant estrogenic activity at all, so this issue is still open to some debate (Ashby et al 1999, Lu & Serrero 1999, Turner et al 1999) and warrants further investigation. Furthermore, as shown in models similar to the SBMC model, prostaglandins may inhibit osteogenesis (Ogiso et al 1992).…”
Section: Differentiationmentioning
confidence: 99%
“…Indeed, it was reported that resveratrol acts as an estrogen agonist 42 ± 44 or antagonist 45 and binds to the estrogen receptor. 46 Thus, we cannot rule out the involvement of a putative receptor in the apoptosisinducing effect of resveratrol.…”
Section: Cell Death and Differentiationmentioning
confidence: 99%